Agroindustry Business Analysis of Ilham Creativepreneur Nature Kerinci (ICN Kerinci) Coffee Perfume in Kemantan Village, Kerinci Regency, Jambi Province, Indonesia - Zelfi Zakir; Sri Wahyuni; Faidil Tanjung (International Journal of Agricultural Sciences, 2020)
This study aims to analyze the ICN Kerinci Coffee Perfume agroindustry. Data collected from June 2019 to August 2019 were analyzed using the descriptive analysis to describe the business profile and quantitative analysis using the variable costing approach to explore profit and breakeven point. The results showed that the ICN Kerinci coffee perfume business is a medium-scale business with ten workers, including business owners as leaders who concurrently marketers and wives as administrative and financial staff. In fulfilling raw materials in green beans from the Robusta type, business owners collaborate with partner farmers. At the time of research, ICN Kerinci only produced one kind of product with two packaging variants, namely Kerinci original perfume for Rp.22,000/pack (45 grams) and an original variant + oil coffee (package) for Rp.35,000/pack. The study suggested expanding the market, especially to Eastern Indonesia, and increasing good cooperation with farmers to ensure the certainty of supply of raw materials; and provide prices based on sorting and grading to stimulate farmers to improve the quality of their green bean products.